DEBATING IN TEACHING SPEAKING SKILL - Herawati, Wiwin (2012)
The study investigates the debating techniques in teaching and learning in the classroom and how debating was taught and practiced in several meetings. This study also investigates teaching learning process to see the significance in the students' speaking skill. It was the students of one state school in Bandung were introduced to debate and how they implemented the rules of debating to improve their speaking skill. This study also reports the process of teaching in debating on the students' speaking skill. The research design used in this study was a case study which portrayed the real situation in the classroom. The data were obtained from interviews, observation, and field notes which were observed for nearly four months and analyzed the students' applying the debate's principles on matter, manner and method. The results shows that debating is an effective media in teaching learning process especially on the students' speaking skill. Based on these findings, this thesis concludes with some specific recommendations for future research. It is recommended that debate can be used in teaching speaking in the classroom and also out of their class in their extracurricular.